Coherent manipulation of coupled electron spins in semiconductor quantum dots. - Petta, JR; Johnson, A; Taylor, J; Laird, E; Yacoby, A; Lukin, MD; Marcus, C; Hanson, M; Gossard, A (2005)
We demonstrated coherent control of a quantum two-level system based on two-electron spin states in a double quantum dot, allowing state preparation, coherent manipulation, and projective readout. These techniques are based on rapid electrical control of the exchange interaction. Separating and later recombining a singlet spin state provided a measurement of the spin dephasing time, T2*, of approximately 10 nanoseconds, limited by hyperfine interactions with the gallium arsenide host nuclei. Rabi oscillations of two-electron spin states were demonstrated, and spin-echo pulse sequences were used to suppress hyperfine-induced dephasing. Using these quantum control techniques, a coherence time for two-electron spin states exceeding 1 microsecond was observed.